The Role of Estrogen Membrane Receptor (G Protein-Coupled Estrogen Receptor 1) in Skin Inflammation Induced by Systemic Lupus Erythematosus Serum IgG - Cai, Zhenming; Xie, Changhao; Qiao, Wei; Fei, Xibin; Guo, Xuanxuan; Liu, Huicheng; Li, Xiaoyan; Fang, Xiang; Xu, Guangqiong; Dou, Hui; Deng, Guo-Min (Frontiers in Immunology, 2017)
Skin injury is the second most common clinical manifestation in patients with systemic lupus erythematosus (SLE). Estrogen may affect the onset and development of SLE through its receptor. In this study, we investigated the role of estrogen and its membrane receptor GPER1 in skin injury of SLE. We found that skin injury induced by SLE serum was more severe in female mice and required monocytes. Estrogen promoted activation of monocytes induced by lupus IgG through the membrane receptor GPER1 which was located in lipid rafts. Blockade of GPER1 and lipid rafts reduced skin inflammation induced by SLE serum. The results we obtained suggest that GPER1 plays an important role in the pathogenesis of skin inflammation induced by lupus IgG and might be a therapeutic target in skin lesions of patients with SLE.